Extreme-user conditions to enhance design creativity and empathy- application using visual impairment. Issue 2 (3rd April 2022) - Raviselvam, Sujithra; Hwang, Dongwook; Camburn, Bradley; Sng, Karen; Hölttä-Otto, Katja; Wood, Kristin L
ABSTRACT: Extreme-users who experience physical, sensory or cognitive challenges can help identify latent needs across a majority of the general population users. Identifying these latent needs may open doors to novel products, services, and systems. Empathic design techniques of simulation tools and scenarios allow designers to experience a range of extreme-user perspectives. However, research still lacks a thorough understanding of the potential impact of such techniques, especially their potential to uncover and address latent needs. This paper strengthens the understanding of simulation tools and scenarios by analyzing two user-centered workshops that applied simulated scenarios to empathize with users with visual impairments (VIs), and uses an empathic similarity metric to evaluate the empathic outcomes in conjunction with self-evaluated empathy. In addition to empathy, creativity is measured for the concepts shared by 36 (x2) workshop participants and 13 participants with VIs. Empirical analysis of the results, across two sequences of controlled studies, supports the potential of simulated scenarios in evoking participant creativity and empathy. KEY TERMINOLOGIES: Empathy: Ability to understand and share feelings of others without judgment. Simulation: Imitation of a process, situation, or circumstance. Scenario: Context-specific (how, where, and who) circumstances experienced by users. Latent Needs: Needs that are important yet not obvious to the average user (Otto & Wood, 1998 ). Extreme-Users: Users who experience challenges with physical or cognitive abilities. General Population: The remainder of the population who do not qualify as extreme-users.